Variations in the N2 Fixation and CH4 Oxidation Activities of Type I Methanotrophs in the Rice Roots in Saline-Alkali Paddy Field Under Nitrogen Fertilization - Jumei Liu; Jiahui Cao; Rina Su; Lei Yan; Kexin Wang; Haiyang Hu; Zhihua Bao (Rice)
Abstract The root-associated methanotrophs contribute to N2 fixation and CH4 oxidation in paddy fields under N-limited conditions. However, the impact of nitrogen inputs on N₂ fixation and CH₄ oxidation by methanotrophs is largely unknown, especially in saline-alkali paddy fields with higher nitrogen application. This study explored the impact of nitrogen fertilization on N₂ fixation and CH₄ oxidation by root-associated active diazotrophic and methanotrophic communities in a saline-alkali paddy field using 15N–N2 and 13C–CH4 isotope feeding experiments along with RNA-based sequencing. The 15N and 13C isotope feeding experiments showed that the CH₄ oxidation-dependent nitrogen fixation rate of methanotrophs (15N and 13C) in the roots of two rice cultivars was significantly higher than the CH₄ oxidation-independent nitrogen fixation rate of heterotrophic diazotrophs (only 15N) under nitrogen fertilization (SN) in a saline-alkali environment (P < 0.05). For Kongyu131 rice, the CH₄ oxidation-dependent nitrogen fixation rate ranged from 1.17 to 4.15 μmol/h/g, while the CH₄ oxidation-independent nitrogen fixation rate was determined to be 1.10 to 3.17 μmol/h/g. In J3 rice, these rates were 7.30 to 9.22 μmol/h/g and 5.76 to 4.85 μmol/h/g, respectively (P < 0.05). Moreover, both N2 fixation and CH4 oxidation rates of methanotrophs in the roots of salt-alkali tolerant J3 cultivar (9.22 μmol/h/g for N2 fixation; 0.09 μmol/h/g for CH4 oxidation) were significantly higher than those in the roots of the common rice cultivar Kongyu131 (4.15 μmol/h/g for N₂ fixation; 0.03 μmol/h/g for CH₄ oxidation) under nitrogen fertilization (P < 0.01). Thus, methanotrophs associated with J3 rice roots demonstrated improved N2 fixation and CH4 oxidation activities under saline-alkali stress in the presence of nitrogen fertilizer. Even heterotrophic diazotrophs in J3 rice roots showed enhanced N2 fixation with (SN) or without (LN) nitrogen inputs. The RNA-based amplicon sequencing showed that nitrogen fertilizer had a greater influence on diazotrophic and methanotrophic communities than the differences between rice cultivars. Further, active Methylomonas (type I methanotrophs) dominated the root-associated diazotrophic (9.8–20.9%) and methanotrophic (46.8–80.3%) communities. Within these, Methylomonas methanica (13.3 vs. 3.8%) and Methylomonas paludis (8.8 vs. 27.4%) were determined as the common genera in the diazotrophic and methanotrophic communities, respectively, with both proportions undergoing significant shifts under SN conditions. Whereas the LN condition led to high CH4 oxidation activity and a relatively high abundance of Methylocystis (26.0%) in the roots of Kongyu131 rice, which sharply decreased under the SN condition (0.3%). The findings revealed that CH4 oxidation-dependent N2 fixation and CH4 oxidation activities of root-associated type I methanotrophs were significantly affected under nitrogen fertilization, with a more pronounced effect in the salt-alkali tolerant J3 rice cultivar compared to Kongyu131. This study highlights the potential of aerobic diazotrophic methanotrophs in enhancing symbiotic diversity and environmental adaptability while contributing to CH4 emission reduction and bioavailable nitrogen accumulation in saline-alkali paddy fields.